Update on EGFR-mutated non-small cell lung cancer - Baik, Christina (Henry Stewart Talks, 2019)
Lung cancer occurrence and distribution, Effectiveness of targeted therapies, Exon 20 mutations, Common mechanisms of resistance, Osimertinib as a treatment for T790M, MET and C797S mutations, Current treatment approaches, Ongoing questions faced by the NSCLC community